Adaptability of photovoltaic mono-polycrystalline solar panels and photovoltaic roof tiles on dwelling roofs of real estate developments - Zalamea León , Esteban; Cuevas Barraza, Cristian (Revista de la Construcción. Journal of Construction, 2019)
The use of photovoltaic (PV) technology in urban areas is an appropriate way to optimize the use of solar energy, since the energy conversion system is located in the same place as the demand. Thus, the losses caused by distribution networks and even technology costs are reduced; in addition, less space is required for energy production in the countryside. Energy can be produced in neighbourhood dwellings located in the periphery in low-density areas that contribute to supplying electricity to high-density urban centres. The performance of a solar system largely depends on the integration capacity of solar panels in building roofs or facades to maximize production. This research has analysed the integration of this type of system in the roofs of new types of housing in developing countries and its adaptability attributable to the geometry of solar panels with regular-sized mono- and polycrystalline cells. This research is based on 32 sloped roof typologies built since 2010. The main results indicate that an average of 36% of the roof surfaces are not useful because of their irregularity; in addition, the small solar panels show more adaptability, although less than expected with respect to large-format PV panels.